Self-organized TiO2 nanotubes on Ti-Nb-Fe alloys for biomedical applications: Synthesis and characterization - Rios, Juliana; Santini, Victor N.; Pereira, Karina D.; Luchessi, Augusto D. [UNESP]; Lopes, Éder S.N.; Caram, Rubens; Cremasco, Alessandra (Elsevier, 2022)
Titanium-based biomaterials with a self-organized titanium oxide (TiO2) surface have received considerable attention in recent years owing to enhanced cellular response and bactericidal behavior promoted by the nanostructured surface. The aim of this study was to investigate the effect of Fe addition on the formation and crystallization of TiO2 nanotubes on Ti-30Nb-xFe substrates and the effect of TiO2 crystallinity on biological behavior. Self-ordered TiO2 nanotubes were prepared by anodization of Ti-30Nb-xFe (x = 0, 3, and 5 wt%) alloys using an aqueous 0.3% HF (vol.%) electrolyte. The nanotube morphology, structure, and composition as a function of the annealing temperature were characterized using FE-SEM, XRD and XPS. The crystallization of nanotubes to the rutile phase occurred at similar temperatures for samples with or without Fe addition, and a mixture of anatase and rutile was observed at 675 °C. The cell viability profile on different surfaces was investigated by MTT and adhesion assays, which revealed improved in vitro response to the crystalline nanotubes.
Keywords: Anodization; Cell-material interaction; Crystallization; Doping; TiO2 nanotubes